Competition between reversible capture of CO₂ and release of CO₂•− using electrochemically reduced quinones in acetonitrile solutions - Tam, Si Man (2022)
The reduced forms of quinones (Q•-/2-) are well-known for their binding affinities toward electrophiles. The ability to modify and add substituents onto quinones to alter their electronic and steric properties allows the optimization of their structures for the highest interactions with electrophiles. Three reduced naphthoquinones with different methyl substitutions of their quinone ring were investigated for their suitability as electrocatalysts for CO2capture and conversion. In the aprotic organic solvent acetonitrile and in the absence of dissolved molecular oxygen, the quinones can be reduced in consecutive one-electron steps to form first the monoanion radicals (Q•-) and then at more negative potentials the dianions (Q2-). When CO2(g) is purged into the solution, the two one-electron reduction processes merge into one two-electron chemically reversible reduction process at the same potential as the first one-electron reduction process observed in an Ar(g) atmosphere. It is proposed that a complex is formed between the reduced quinone andnCO2molecules, [Q(CO2)n]2-, that allows the dianion to be formed at a lower energy (voltage) compared to under an Ar(g) atmosphere. The binding is completely chemically reversible so that purging the solutions of [Q(CO2)n]2-with Ar(g) results in the carboxylated complex dissociating according to two major pathways. Pathway (A) involves the generation of Q2-(or Q•-) and CO2(g), while pathway (B) results in the negative charge transferring to the CO2molecules to form the carboxyl radical anion, CO2•-, and the neutral Q.